Evolution and utility of preimplantation genetic testing for monogenic disorders in assisted reproduction - A narrative review - Firuza R Parikh; Arundhati S Athalye; Dhananjaya K Kulkarni; Rupesh R Sanap; Suresh B Dhumal; Dhanashree J Warang; Dattatray J Naik; Prochi F Madon (Wolters Kluwer Medknow Publications, 2021)
Preimplantation genetic testing (PGT) for monogenic disorders and assisted reproductive technology have evolved and progressed in tandem. PGT started with single-cell polymerase chain reaction (PCR) followed by fluorescent in situ hybridisation for a limited number of chromosomes, later called 'preimplantation genetic diagnosis (PGD) version 1'. This review highlights the various molecular genetic techniques that have evolved to detect specific inherited monogenic disorders in the preimplantation embryo. Literature review in English was performed in PubMed from 1990 to 2021, using the term 'preimplantation genetic diagnosis'. With whole-genome amplification, multiple copies of embryonic DNA were created. This helped in avoiding misdiagnosis caused by allele dropout. Multiplex fluorescent PCR analysed informative short tandem repeats (STR) and detected mutations simultaneously on automated capillary electrophoresis sequencers by mini-sequencing. Comparative genomic hybridisation (CGH) and array CGH were used for 24 chromosome aneuploidy screening. Subsequently, aneuploidies were detected by next-generation sequencing using single-nucleotide polymorphism arrays, while STR markers were used for haplotyping. 'PGD version 2' included accurate marker-based diagnosis of most monogenic disorders and detection of aneuploidy of all chromosomes. Human leukocyte antigen matching of embryos has important implications in diagnosis and cure of haemoglobinopathies and immunodeficiencies in children by means of matched related haematopoietic stem cell transplantation from an unaffected 'saviour sibling' obtained by PGT.